2014
DOI: 10.12973/eu-jer.3.3.111
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on Students Academic Performance for Junior Secondary Schools in Botswana

Abstract: The major purpose of the study was to investigate factors which contribute to the decline in students' academic performance in junior secondary schools in Botswana since 2010. The study was mainly quantitative and used the positivist inquiry paradigm. The study employed critical theory for its theoretical framework. Questionnaires were used to gather data from two hundred participants. Some documents were analyzed to supplement the information collected through the questionnaire. Data were analysed using the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 6 publications
1
22
0
1
Order By: Relevance
“…Increasing the practical content may expose students to the real life experiences in learning agriculture as a subject and may generate student interest in learning agriculture. Tutoring is another strategy suggested for improving students' achievement (Mphale & Mhlauli, 2014). Some slow learners may need extra help in order to understand the content, which requires extra time and attention.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Increasing the practical content may expose students to the real life experiences in learning agriculture as a subject and may generate student interest in learning agriculture. Tutoring is another strategy suggested for improving students' achievement (Mphale & Mhlauli, 2014). Some slow learners may need extra help in order to understand the content, which requires extra time and attention.…”
Section: Discussionmentioning
confidence: 99%
“…Boipono and Margret (2014) reported that teacher pedagogy skills, teacher training in agriculture and availability of teaching and learning materials are the major causes of poor performance of students in Agriculture in Botswana. Mphale and Mhlauli (2014) identified the contributing factors to poor performance as inadequate resources, the low morale of teachers, lack of parental involvement, lack of preparedness among teachers and students for any change, lack of incentives for teachers, lack of seriousness among students about their work, improper assessment and lack of support for homework. Kobote (2014) did not show a clear trend in the performance of students in Tanzania rural and urban schools; performance was poor in the rural schools whereas the performance of girls was poorer than that of boys in urban schools.…”
Section: The Causes To Poor Academic Performance and Ways To Improvementioning
confidence: 99%
See 2 more Smart Citations
“…Education is an important prerequisite to human development in the modern knowledge millennium. Previous studies have shown how education promoted human development and was seen by many to be in the center of any society's life and concern (MolokoMphale & Mhlauli, 2014). Similarly, Al-Shuabi (2014) noted that education is an conducted by Yusuf (2012) asserted that success of any educational institution is measured by the performance of its students.…”
Section: Introductionmentioning
confidence: 99%